Greetings from Trinidad and Tobago - Thomas, H.O. (H.O. Thomas, 2009)
Description on the back of the postcard reads: "Sun worshippers curvet in the sun, sea and sand at Trinidad's delightful Las Cuevas Beach, situated on the scenic North Coast, Trinidad, W.I.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Palms--Trinidad and Tobago; Beaches--Trinidad and Tobago; Coasts--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Las Cuevas